[Compilado de obras de Tadao Ando] (The Japan Architect)
Se compilan obras del arquitecto Tadao Ando. Contiene: Koshino Residence, 1981. Kojima Housing, 1981. Matsumo Residence, 1980. Okusu Residence, 1978. Onishi, 1979. Rokko Housing, 1982. House with Territory-delineating Walls, 1977. House at Tezukayama, 1977. House in Two Concrete Blocks, 1979. Axial Symmetry in Concrete, 1979. Ishihara Residence, 1978. Horiuchi Residence, 1979. Fuku Residence, 1980. New Version of the Old Row House, 1976. Tezukayama Tower Plaza, 1976. Steps Upward Through Light, 1980. Okamoto Housing Project, 1976. Art Gallery Complex Project, 1977.